Analysis of driver gene mutations in oesophageal squamous cell carcinoma - Shipanga, Hendrina Nelao Mwiiwete (Department of Integrative Biomedical Sciences, 2026)
Oesophageal cancer (OC) is the eleventh most diagnosed cancer and the seventh most common cause of cancer-related deaths worldwide. The two main subtypes are oesophageal adenocarcinoma (OAC) and oesophageal squamous cell carcinoma (OSCC). OAC is more common in North America and Europe, while OSCC predominantly occurs in Eastern Asia, Sub-Saharan Africa and Latin America. Over 80% of the OSCC cases and deaths worldwide occur in less developed regions, including Sub-Saharan Africa. The asymptomatic development of OSCC, results in late diagnosis of the disease with a poor prognosis, typically ranging from 5-10% at 5-year post-diagnosis in Africa. This study investigated the genomic landscape of OSCC in the South African population by whole-genome sequencing (WGS) and whole-exome sequencing (WES). Normal and tumour DNA and RNA was isolated from OSCC patient biopsies prior to the commencement of any form of chemotherapy or radiotherapy. WGS was performed on 31 samples, while WES was conducted on 67 samples. The mRNA levels of selected genes in OSCC were quantitated by RT-qPCR. KYSE30 cells were used for siRNA-mediated knockdown experiments targeting p14ARF and p16INK4a in OSCC. In silico structural analysis of missense mutations in p14ARF and p16INK4a was conducted using UCSF Chimera tool. WGS analysis identified 35 frequently mutated genes in OSCC, among these, TP53, CDKN2A.p16INK4a, CDKN2A.p14ARF, and KMT2D were identified as OSCC driver genes. Based on the mutation spectrum analysis, samples clustered into two distinct groups, cluster 1 and cluster 2b, characterized by TP53 alterations and mutation rates per megabase (Mb). WES expanded findings across 67 samples, identifying TP53, NFE2L2, CDKN2A.p16INK4a, ZNF750, and NOTCH1 as OSCC driver genes. Samples clustered into three groups: cluster 1, cluster 2a, and cluster 2b, expanding upon the two clusters identified in our WGS analysis. In both WGS and WES analyses, cluster 1 exhibited TP53 mutations and relatively high somatic mutation rates per Mb, while cluster 2 lacked TP53 mutations. Cluster 2 is further subdivided into clusters 2a and 2b in WES. Cluster 2a samples display a high mutation rate per Mb, while cluster 2b samples display fewer genomic alterations. By quantifying the contribution of the mutational signatures to the mutation spectrum, we found a relatively high contribution of mutation signature SBS1, SBS2, and SBS13, implicating aging and AID/APOBEC (activation induced cytidine deaminase/apolipoprotein B mRNA editing enzyme catalytic subunit) activation in OSCC tumourigenesis. WGS analysis revealed three novel mutational signatures that had not been previously identified. Interestingly, these signatures were not observed in the samples analysed by WES, even though the WES cohort included a larger sample size. The significance of these novel mutational signatures remains unclear. Evaluation of selected differentially expressed genes in OSCC involved in cell cycle control, the KEAP1-NFE2L2 (NRF2) pathway, and DNA damage response pathways showed variable expression of these genes in OSCC suggests potential dysregulation of the genes in OSCC. Furthermore, p16INK4a and p14ARF mRNA levels were significantly lower in 61% and 48% of OSCC tumour samples, respectively, while elevated levels were observed in 16% and 25% of tumours, respectively. Knockdown of p14ARF and p16INK4a in KYSE30 cells resulted in dysregulation of key regulators involved in multiple cancer signalling pathways, including cell cycle, apoptosis, and KEAP1-NFE2L2 pathways. This dysregulation could promote cell survival, growth of apoptosis-resistant cells, and resistance to stress, which are critical events in tumorigenesis. In-silico mutation analysis revealed damaging mutations in p16INK4a, such as p.A68V, p.D84N, p.D108H, p.D108N, p.D108Y, and p.L130P. These mutations cause significant structural alterations that disrupt interactions crucial for p16INK4a stability and function, possibly affecting cell cycle regulation and potentially promoting tumorigenesis in OSCC. Our findings highlights novel molecular features of OSCC and provides comprehensive insights into the genomic and molecular mechanisms driving OSCC within the South African population